Pendampingan Pembuatan Konten Visual Digital bagi UMKM di RW 11 Kelurahan Semolowaru - Tukiman, Tukiman; Putri, Novita Anggraini; Putriawan, Faisa Syahda (Jurnal Gema Ngabdi, 2025)
The rapid advancement of digital technology has driven Micro, Small, and Medium Enterprises (MSMEs) to adapt their marketing strategies, especially through visually-oriented social media platforms. However, many MSME actors still face challenges in creating compelling promotional content. This community service activity aimed to build the capacity of MSMEs in RW 11, Semolowaru Subdistrict, Surabaya, in producing professional visual content such as photos and videos. The methods used included an initial survey, participatory socialization, and hands-on mentoring. The results indicated an increase in participants' understanding and skills, marked by improved visual quality and greater confidence in digital product promotion. This program is expected to support local MSMEs in initiating digital transformation and enhancing their competitiveness in a wider market.